Hubungan Jumlah Sel Mast dengan Tampilan Ekspresi Vascular Endothelial Growth Factor (VEGF) pada Cutaneous Squamous Cell Carcinoma - Delyuzar; Soekimin; Edi Kerina Sembiring, (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2019)
BackgroundThe most common non-melanocytic skin cancers are basalioma and squamous cell carcinoma. Squamouscell carcinoma is a malignancy of squamous epithelium. Mast cells stimulate neovascularization andangiogenesis in multiple tumors. One of the main factors of angiogenesis in squamous cell carcinoma isthe Vascular Endothelial Growth Factor (VEGF). The aim of this study is to investigate the associationbetween number of mast cells with the expression of VEGF of cutaneous squamous cell carcinoma.MethodsThis is an analytical descriptive study with cross sectional approach. The sample of this study are paraffinblocks of skin tissue which diagnose histopathologically as squamous cell carcinoma. Then the sampleswill be stained with immunohistochemistry CD117 (Novocastra®) to count the number of mast cells andVEGF (Dako®) to see angiogenesis. Their expression will be analyzed with Fisher’s Exact Test statisticalanalysis to investigate the association between number of mast cells with expression of VEGF ofcutaneous squamous cell carcinoma.ResultsThe number of mast cells ≥15 cells were 7 cases (23.3%). Expressed VEGF positive expression in 30cases (100%). Suitability test Fischer's Exact Test has value not significant (p> 0.05).ConclusionThere is no conformance relationship between the number of mast cells with VEGF expression of p-value.